A ‘Bermuda Triangle’ Effect Shaping Reef Fish Connectivity Across the Western Atlantic - Melissa Scheel‐Dalmau; Jose Julian Tavera; Kenyon C. Lindeman; David Snyder; Claudio Oliveira; Struan R. Smith; Carmen del Rocío Pedraza‐Marrón; Arturo Acero P; Ricardo Betancur‐R (Molecular Ecology, 2026)
Understanding the spatial scale and structure of marine connectivity is essential for uncovering how ocean currents shape gene flow, population structure and larval transport in reef organisms. We examined range‐wide patterns of gene flow and population structure in the tomtate ( Haemulon aurolineatum ), an abundant reef fish with a broad distribution from southern Brazil to Bermuda in the western Atlantic. We used genome‐wide SNPs, mitochondrial DNA sequences and a re‐evaluation of morphological variation to assess connectivity, demographic history and lineage boundaries across 22 locations spanning all major biogeographic provinces within the species' range. Population structure and phylogenetic analyses identified three main genetic groups: (1) the Caribbean and Southwestern Atlantic (CSA), (2) the Gulf of Mexico (GOM) and (3) Bermuda (BDA), with further substructure within CSA. Demographic modelling and migration analyses supported early divergence followed by sustained but asymmetric gene flow, particularly into BDA, which acts as a long‐term demographic sink, likely maintained by episodic larval input from CSA and GOM. This pattern aligns with previous findings from biophysical models and larval transport studies. Recognized marine barriers such as the Eastern and Western Caribbean breaks contributed to population differentiation, while coastal corridors along Brazil and the Guianas facilitated northward gene flow. Coalescent‐based species delimitation supported three species‐level lineages, but we interpret these as subspecies: morphologically and genomically distinct, yet not fully reproductively isolated. Taken together, these results demonstrate how asymmetric dispersal and oceanographic isolation can structure genetic diversity in marine organisms by creating peripheral demographic sinks like Bermuda, where limited and unidirectional connectivity promotes long‐term differentiation—a pattern we describe as the ‘Bermuda Triangle effect.’

Effects of aerobic exercise and cardiorespiratory fitness on white matter free water fraction in older adults: a 1-year randomized controlled trial - Takashi Tarumi; Junyeon Won; Tsubasa Tomoto; Norman Scheel; David C. Zhu; John Ashley; Karen M. Rodrigue; Kristen M. Kennedy; Denise C. Park; Rong Zhang (GeroScience, 2025)

Hold it close: male octopus hold their hectocotylus closer to their body - Willem Lee Weertman; David Scheel (Marine Biology, 2024)
The right third arm of the male octopus is the hectocotylized arm. This arm is modified by anatomy specialized to hold and transfer sperm packets to the female, and lacks suckers at the distal end. Male octopus may be distinguished by the skilled eye from their habit of holding their hectocotylus closer to their body in a protective manner, although this observation has never been described quantitatively. We utilized a three-step process of data annotation, pose estimation model training, and model inference to show that this common observation is true of Octopus rubescens . In 2338 images, the eyes, mantle tip, and arm tips of two male ( n = 1152) and three female ( n = 1085) octopuses were annotated by an experimenter. These images were then used to train a DeepLabCut pose estimation model which achieved a RMSE of 1.78 cm. This model was then used to annotate 11.4 h ( n = 408,985 images) of four female and eight male octopuses moving across the middle of a large aquarium. We then compared the human annotated data, and the model inference data separately. In both datasets we compared the arm-tip-to-eye centered point distances, as well as the octopus centric arm tip 90% kernel density estimation area. In both the training dataset and the model inference datasets we found common results. Male O. rubescens hold their third to the right arm closer to their body than all seven other arms while the females do not. Further, in both males and females, the rear arm pairs operate closer to the body than the front arm pairs. Despite their anatomical similarity and potential redundancy, these results indicates functional differences in arm use by octopuses.

Towards global traceability for sustainable cephalopod seafood - Ian G. Gleadall; Hassan Moustahfid; Warwick H. H. Sauer; Lahsen Ababouch; Alexander I. Arkhipkin; Jilali Bensbai; Isa Elegbede; Abdelmalek Faraj; Pedro Ferreiro-Velasco; Roberto González-Gómez; Carmen González-Vallés; Unai Markaida; et al. (Marine Biology, 2024)

Characteristics of Habitats Used by Enteroctopus dofleini in Prince William Sound and Cook Inlet, Alaska - David Scheel (Marine Ecology, 2002)
Habitat characteristics associated with the giant Pacific octopus, Enteroctopus dofleini (Wülker 1910), were studied in Prince William Sound and Port Graham, Alaska, from beach walk, SCUBA and submersible surveys at depths of 0 to 197 m. Octopus counts on beach walk transects were positively correlated with soft substrates (sand, gravel or broken rubble), the presence of boulders, and dense kelp cover immediately offshore of the transect; and negatively correlated with depth on SCUBA transects. No significant habitat correlations were found with counts on submersible transects. On beach walks, octopus counts were reduced on hard substrates to 38 % of the counts on soft substrates. Counts increased five‐fold in the presence of boulders over counts in their absence, and increased fifteen‐fold adjacent to dense (> 75 %) kelp cover over counts adjacent to sparse ( 2 . These densities were only 1 to 50 % of densities of the same species recorded in British Columbia in the late 1970s and early 1980s. Few data are available to test recruitment, mortality, and habitat selection hypotheses that would account for differences between habitats. However, the presence of the highest octopus densities in intertidal and very shallow subtidal areas indicates the likely importance of near‐shore, shallow‐water habitats, and highlights the vulnerability of octopus populations to changes in these habitats.